Endothelial β-Catenin Signaling Supports Postnatal Brain and Retinal Angiogenesis by Promoting Sprouting, Tip Cell Formation, and VEGFR (Vascular Endothelial Growth Factor Receptor) 2 Expression. Issue 11 (November 2019) - Martowicz, Agnieszka; Trusohamn, Marta; Jensen, Nina; Wisniewska-Kruk, Joanna; Corada, Monica; Ning, Frank Chenfei; Kele, Julianna; Dejana, Elisabetta; Nyqvist, Daniel
Abstract : Objective: Activation of endothelial β-catenin signaling by neural cell-derived Norrin or Wnt ligands is vital for the vascularization of the retina and brain. Mutations in members of the Norrin/β-catenin pathway contribute to inherited blinding disorders because of defective vascular development and dysfunctional blood-retina barrier. Despite a vital role for endothelial β-catenin signaling in central nervous system health and disease, its contribution to central nervous system angiogenesis and its interactions with downstream signaling cascades remains incompletely understood. Approach and Results: Here, using genetically modified mouse models, we show that impaired endothelial β-catenin signaling caused hypovascularization of the postnatal retina and brain because of deficient endothelial cell proliferation and sprouting. Mosaic genetic analysis demonstrated that endothelial β-catenin promotes but is not required for tip cell formation. In addition, pharmacological treatment revealed that angiogenesis under conditions of inhibited Notch signaling depends upon endothelial β-catenin. Importantly, impaired endothelial β-catenin signaling abrogated the expression of the VEGFR (vascular endothelial growth factor receptor)-2 and VEGFR3 in brain microvessels but not in the lung endothelium. Conclusions: Our study identifies molecular crosstalk between the Wnt/β-catenin and the Notch and VEGF-A signaling pathways and strongly suggest that endothelial β-catenin signaling supports central nervous system angiogenesis by promoting endothelial cell sprouting, tip cell formation, and VEGF-A/VEGFR2 signaling. Abstract : Supplemental Digital Content is available in the text.